Transition from early intervention program to primary school in children with autism spectrum disorder. - Eapen, V.; Grove, R.; Aylward, E.; Joosten, Annette; Miller, S.; Van Der Watt, G.; Fordyce, K.; Dissanayake, C.; Maya, J.; Tucker, M.; DeBlasio, A. (2017)
AIM: To evaluate the characteristics that are associated with successful transition to school outcomes in preschool aged children with autism. METHODS: Twenty-one participants transitioning from an early intervention program were assessed at two time points; at the end of their preschool placement and approximately 5 mo later following their transition to school. Child characteristics were assessed using the Mullen Scales of Early Learning, Vineland Adaptive Behaviour Scales, Social Communication Questionnaire and the Repetitive Behaviour Scale. Transition outcomes were assessed using Teacher Rating Scale of School Adjustment and the Social Skills Improvement System Rating Scales to provide an understanding of each child's school adjustment. The relationship between child characteristics and school outcomes was evaluated. RESULTS: Cognitive ability and adaptive behaviour were shown to be associated with successful transition to school outcomes including participation in the classroom and being comfortable with the classroom teacher. These factors were also associated with social skills in the classroom including assertiveness and engagement. CONCLUSION: Supporting children on the spectrum in the domains of adaptive behaviour and cognitive ability, including language skills, is important for a successful transition to school. Providing the appropriate support within structured transition programs will assist children on the spectrum with this important transition, allowing them to maximise their learning and behavioural potential.